Community-Based Tourism Development: Mount Bismo Ecotourism Development Program in Sikunang Village, Kejajar District, Wonosobo Regency - Fabian, Fachmi; Abdullah, Faqih Nur (Prospect Publishing, 2024)
Sikunang Village, which is located in Kejajar District, Wonosobo Regency, Central Java Province, has a very potential landscape. The Sikunang Village area is included in the Dieng Plateau area which has the potential for a mountainous landscape. One of them is a mountain in the Sikunang Village area, namely Mount Bismo. However, this potential has not been felt optimally by the residents of Sikunang Village. This is due to a lack of skills in managing tourist and climbing areas in the region. Apart from that, economic factors also influence the condition of the people in Sikunang Village, where some residents live below the poverty line and are unemployed. Responding to these problems, PT Geo Dipa Energi (Persero) Dieng Unit through its CSR program implemented a community empowerment program based on ecotourism development. The program entitled